Experiences and psychological health among children exposed to online child sexual abuse – a mixed methods study of court verdicts - Joleby, Malin (Psychology, crime & law, 2021)
Cases of online child sexual abuse (OCSA) are increasing dramatically in number, but research on this relatively new type of crime and its psychological consequences is limited, leading to major challenges for the judiciary. The present mixed methods study investigated 98 legal cases of OCSA (children aged 7-17 years, M = 12.3, SD = 1.92) in Swedish District Courts to see if and how children's experiences and psychological health were described in the written verdicts. The results revealed that the children's psychological health was mentioned in less than half (48.0%) of the cases. Thematic analyses identified several potential vulnerability factors (e.g. poor psychological health, low self-esteem, loneliness) and several potential psychological consequences (e.g. psychological suffering, self-harming and/or suicidal behavior, internalized self-loathing, impaired relationships) among the children, all of which were similar to what research has shown among victims of offline CSA. The sexual abuse situation was often perceived as threatening, and many children felt that they had no other choice than to comply. In addition, the sexually abusive act was depicted as distressing and sometimes painful. In light of these findings, we suggest that OCSA should not be viewed as essentially different or less severe than offline CSA.